Peningkatan Kinerja Aparatur melalui Kompetensi dan Pengawasan: Bukti Empiris dari Layanan Perlindungan Konsumen - Mintoro Rutadi; Sri Rahayu; Rifda Fitrianty (BISMA : Business and Management Journal, 2026)
Employee performance in the public sector is a crucial factor in achieving effective and accountable public services. However, previous studies on the influence of competence and supervision on employee performance have produced inconsistent findings, particularly in public service organizations with technical and regulatory responsibilities. This study aims to examine the effects of competence and supervision on the performance of employees at the Consumer Protection Technical Implementation Unit (UPT) in Bojonegoro. A quantitative survey approach was employed, and primary data were collected from 125 respondents selected through simple random sampling using a Likert-scale questionnaire. Data were analyzed using multiple linear regression preceded by classical assumption tests. The results indicate that competence (β = 0.386; p < 0.05) and supervision (β = 0.369; p < 0.05) have a positive and significant effect on employee performance. Competence was found to have a more dominant influence than supervision. The Adjusted R² value of 0.628 shows that both variables jointly explain 62.8% of the variance in employee performance. These findings highlight the importance of strengthening employee competence through continuous technical training and enhancing supervision through periodic evaluation systems to improve the quality of public service delivery.